Human Papillomavirus Research in a Global Perspective - Rajkumar, Rajamanickam (IntechOpen, 2016)
This book is a feast of knowledge, yet a balanced diet of healthy foods. There are high values of rich essential nutrients from top-quality medical research. But they are made easily digestible and absorbable, even by health care providers and planners, working in resource-limited settings, in all parts of the world, through social implications and community applications. All the chapters are value-added master pieces. The book would serve both as a scientific reference guide and a practical work manual. The authors, editor, and Intech publishers, together, are pleased to provide the readers a precious blend of scientific excellence and social relevance, for health empowerment, globally. We wish the readers great success, savoring science and sociology together.